Choline Deficiency Attenuates Body Weight Gain and Improves Glucose Tolerance in ob/ob Mice - Gengshu Wu; Liyan Zhang; Tete Li; Gary Lopaschuk; Dennis E. Vance; René L. Jacobs (Journal of Obesity)
Previous studies demonstrated that choline supply is directly linked to high-fat-diet-induced obesity and insulin resistance in mice. The aim of this study was to evaluate if choline supply could also modulate obesity and insulin resistance caused by a genetic defect. Eight-week-old male ob/ob mice were fed for two months with either choline-deficient or choline-supplemented diet. Tissue weight including fat mass and lean mass was assessed. Intracellular signaling, plasma glucagon and insulin, and glucose and insulin tolerance tests were also investigated. The choline-deficient diet slowed body weight gain and decreased fat mass. Choline deficiency also decreased plasma glucose level and improved glucose and insulin tolerance although fatty liver was exacerbated. Increased adipose lipolytic activity, decreased plasma glucagon and reduced expression of hepatic glucagon receptor were also observed with the choline-deficient diet. Our results demonstrate that a choline-deficient diet can decrease fat mass and improve glucose tolerance in obese and diabetic mice caused by a genetic defect.